Legal aspects and forensic prevention of illegal participation in entrepreneurial activity (on the example of kazakhstan and belarus) - Khlus, A.M. (Bulletin of the Karaganda University “Law Series”, 2025)
The analysis of criminal law norms providing for liability for illegal participation in entrepreneurial activity contained in the Criminal Codes of Kazakhstan and Belarus is carried out. Attention is focused on some of the reasons and conditions that contribute to the commission of the crime under study. A proposal is made to improve the legal norm establishing criminal liability for this type of corruption crimes. The need to consolidate in the criminal procedure codes of Kazakhstan and Belarus the obligation of the subject carrying out the preliminary (pre-trial) investigation to take response measures in each case of identifying the causes and conditions (circumstances) of committing any type of crime is substantiated. The author pointed out the possibility of implementing preventive measures in the process of investigating the crime under study by conducting a preventive conversation during the interrogation. The main forms of preventive activities of the subject carrying out the preliminary (pre-trial) investigation are legal and forensic education. The expediency of implementing preventive measures outside the investigated criminal case on illegal participation in entrepreneurial activity is indicated. The objects of preventive impact are the organization (institution) in which the corruption crime was committed, its management and employees (employees) of this organization.